Socio-Economic Benefits of Microgravity Research - Afolayan, E. M.; Oluwafemi, F. A.; Jeff-Agboola, E. O.; Oluwasegun, T.; Ayankale, J.O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Microgravity researches are conducted in low gravity environments. These low gravity environments can be achieved in a number of ways including parabolic aircraft flights, sounding rockets, drop towers, clinostat. Gravity dominates everything on Earth, from the way life has developed to the way materials interact. The reduction of gravity causes significant changes in the chosen sample which could be cells, plants, micro-organisms and small samples from material sciences. The changes that occur as a result of the effect of microgravity have led to discoveries that have been found to be of socio-economic benefits. Socio-economic benefits involve benefits in wealth, health, economic, environment. Sustainable development in an economy includes economic growth, environmental protection and social equality. Space technology applications such as in microgravity stimulate economic growth and improve the quality of life of people, in this way, it is beneficial to mankind. Overall, products manufactured in microgravity environments have key properties usually surpassing the best terrestrial counterparts. Commercially, these products have attractive features that facilitate marketing. This review considers the various benefits of microgravity research in life-sciences such as in microbiology, pharmacy, and medicine.